Asymptomatic Bacteriuria during Pregnancy: Causative Agents and Their Sensitivity in Rajshahi City - Selimuzzaman, ABM; Ullah, MA; Haque, MJ (TAJ: Journal of Teachers Association, 2009)
This was a cross-sectional study conducted among the pregnant mothers of 2nd trimester in the metropolitan area of Rajshahi city. Total 2000 apparently healthy pregnant mothers were selected by random sampling with the view to estimate the prevalence of asymptomatic bacteriuria in apparently healthy pregnancy, its causative agents and their sensitivity pattern in the Rajshahi city. These 2000 pregnant mothers were selected from 20 wards by applying 2-stage random sampling. Two consecutive morning midstream urine samples were collected for culture and sensitivity test. The prevalence of asymptomatic bacteriuria in the rural Rajshahi was 14.5%. E.Coli was the commonest causative bacteria (94.83%). The urinary pathogens causing asymptomatic bacteriuria in pregnancy in the Rajshahi city were resistance to amoxicillin, cephalexin and cephradine, moderately sensitive to doxycycline and highly sensitive to ciprofloxacin, gentamicin, nitrofurantoin and nalidixic acid. Screening of asymptomatic bacteriuria in pregnancy must be considered as an essential part of antenatal care like routine checkup for albumin and sugar in urine in this city community. doi: 10.3329/taj.v19i2.3153 TAJ 2006; 19(2): 66-69